2017
DOI: 10.1002/jcb.26181
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐377 Regulates Inflammation and Angiogenesis in Rats After Cerebral Ischemic Injury

Abstract: Ischemic stroke is the leading cause of disabilities worldwide. MicroRNA-377 (miR-377) plays important roles in ischemic injury. The present study focused on the mechanisms of miR-377 in protecting ischemic brain injury in rats. Cerebral ischemia was induced by middle cerebral artery occlusion (MCAO) in rats. Primary rat microglial cells and brain microvascular endothelial cells (BMECs) were exposed to oxygen-glucose deprivation (OGD). The concentrations of cytokines (TNF-α, IL-1β, IL-6, IFN-γ, TGF-β, MMP2, CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 52 publications
2
45
0
Order By: Relevance
“…Besides, Mirt2 overexpression restored the level of miR-377 which was repressed by IFN-c. miR-377 has been reported to promote white adipose tissue inflammation in mice models [16]. Besides, miR-377 relieves the cerebral inflammation and thereby lessens the ischemic brain injuries [15]. Similar results were observed in renal ischemia-reperfusion injury mice model [16] and retinal endothelial cell model [26].…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Besides, Mirt2 overexpression restored the level of miR-377 which was repressed by IFN-c. miR-377 has been reported to promote white adipose tissue inflammation in mice models [16]. Besides, miR-377 relieves the cerebral inflammation and thereby lessens the ischemic brain injuries [15]. Similar results were observed in renal ischemia-reperfusion injury mice model [16] and retinal endothelial cell model [26].…”
Section: Discussionsupporting
confidence: 65%
“…Consistently, our results showed that enforcing Mirt2 expression protected SGECs against IFN-c-induced inflammatory insults. Given that miR-377 has been reported to regulate inflammation in cerebral ischemic injury rats model [15], we consequently focused on the regulatory relationship between miR-377 and Mirt2 in the biological progresses. It was noteworthy that Mirt2 protected SGECs against inflammatory insults by elevating miR-377.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-377 plays a proinflammatory role following ischemic stroke by modulating the anti-inflammation effect of EGR2 and the proangiogenesis effect of vascular endothelial growth factor (VEGF) (71). Fan et al (71) found that the level of miR-377 decreased in the rat brain after MCAO and cultured microglia cells exposed to OGD. Furthermore, they found that miR-377 knockdown could attenuate microglia activation and the release of proinflammatory cytokines after OGD.…”
Section: The Mirna-mediated Neuroinflammatory Events Under Hypoxia/ismentioning
confidence: 99%
“…microRNAs (miRNAs), a family of highly conserved small non-coding RNAs directly binding to the 3′-untranslated regions (3′-UTRs), could mediate target genes, protein expression, and signaling pathways to affect cell functions such as proliferation, apoptosis, differentiation, migration, and invasion, thereby contributing to multiple biological processes, such as inflammation formation and immune response. [5][6][7][8] Accumulating evidences have proven that several miRNAs have established their value on the progress of various immune diseases, including RA, systemic lupus erythematosus (SLE), and psoriasis, which uncovered the potential of miRNA as marker for RA progression and prognosis. [9][10][11][12][13][14][15] However, no studies investigate the effect of comprehensive miRNA expression profile on predicting clinical response to TNF inhibitor in RA patients.…”
Section: Introductionmentioning
confidence: 99%